2018
DOI: 10.1097/igc.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1, Ki67, and β-Catenin Immunoexpression Is Not Related to Differentiation, Platinum Response, or Prognosis in Women With Low- and High-Grade Serous Ovarian Carcinoma

Abstract: Ki67 expression was significantly higher in HGSOC. BRCA1 and β-catenin expression did not differ between LGSOC and HGSOC samples. BRCA1, Ki67, and β-catenin expression was neither related to clinicopathological features, response to platinum-based chemotherapy, nor survival. Only International Federation of Gynecology and Obstetrics stage remained associated with poor survival in women with HGSOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(70 reference statements)
1
7
1
Order By: Relevance
“…The recent study by Chen et al, involving 318 patients with high-grade serous ovarian cancer, showed an association between low Ki67 expression and platinum resistance 8. Sallum et al reported no difference in Ki67 expression among patients with platinum-sensitive or platinum-refractory/resistant low-grade and high-grade serous ovarian cancer 14. In contrast, our data show an association between lower Ki67 expression and more frequent TFI of >6 months.…”
Section: Discussioncontrasting
confidence: 74%
“…The recent study by Chen et al, involving 318 patients with high-grade serous ovarian cancer, showed an association between low Ki67 expression and platinum resistance 8. Sallum et al reported no difference in Ki67 expression among patients with platinum-sensitive or platinum-refractory/resistant low-grade and high-grade serous ovarian cancer 14. In contrast, our data show an association between lower Ki67 expression and more frequent TFI of >6 months.…”
Section: Discussioncontrasting
confidence: 74%
“…A total of 44 studies were included in this systematic review 10 12 13 18–58. The flow chart outlining the study design is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…LGSC constitutes a smaller group of epithelial ovarian cancer, and are generally treated as the high-grade serous counterpart [7-10,13,17,18]. Gockley et al [19], identified 16,854 (95.7%) patients with high-grade serous ovarian cancer (HGSC) and 755 (4.3%) patients with LGSC from the National Cancer Database [19].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data underlined that LGSC are characterized by partial chemoresistance [3-6]. Few studies reported outcomes of patients affected by LGSC and limited data are still available on prognosis of patients affected by advance stage LGSC (stage IIIB–IV) [678910111213].…”
Section: Introductionmentioning
confidence: 99%